2016
DOI: 10.15330/pcss.17.4.575-581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser irradiation on Electrochemical Properties of composite MoS2/C

Abstract: Вплив лазерного опромінення на електрохімічні властивості композиту MoS 2 /СДВНЗ «Прикарпатський національний університет імені Василя Стефаника», вул. Шевченка, 57, м. Івано-Франківськ, 76018 У роботі представлено результати досліджень електрохімічних властивостей композиту MoS 2 /C. Показано, що вклад у провідність композитів вносить як ємнісний характер накопичення заряду, притаманний високопровідному вуглецю, який, розташовуючись між шарами MoS 2 , покращує перенесення заряду під час процесів заряд/роз… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…By changing the parameters of laser irradiation (energy, pulse duration, wavelength) it is possible to obtain the material with specified characteristics. It was found that the laser irradiation of molybdenum sulfide and its composite with carbon material for 3, 5 and 7 min leads to improved specific electrochemical characteristics [15]. Namely, the laser irradiation for 7 min of MoS2/C composite leads to an increase in its discharge specific capacitance at a scan rate of 1 mV/s by 50%, which is associated with an increase in structural defects and activation of charge carriers under the influence of laser.…”
Section: Introductionmentioning
confidence: 98%
“…By changing the parameters of laser irradiation (energy, pulse duration, wavelength) it is possible to obtain the material with specified characteristics. It was found that the laser irradiation of molybdenum sulfide and its composite with carbon material for 3, 5 and 7 min leads to improved specific electrochemical characteristics [15]. Namely, the laser irradiation for 7 min of MoS2/C composite leads to an increase in its discharge specific capacitance at a scan rate of 1 mV/s by 50%, which is associated with an increase in structural defects and activation of charge carriers under the influence of laser.…”
Section: Introductionmentioning
confidence: 98%